Calcium Channel Blocker–Clarithromycin Drug Interaction Did Not Increase the Risk of Nonvertebral Fracture: A Population-Based Study. (February 2015) - Fraser, Lisa-Ann; Shariff, Salimah Z.; McArthur, Eric; Naylor, Kyla L.; Garg, Amit X.
Background: Calcium channel blocker (CCB) use in elderly patients lowers blood pressure and can increase the risk of falls and fractures. These drugs are metabolized by the cytochrome P450 3A4 (CYP3A4) enzyme, and blood concentrations of these drugs may rise to harmful levels when CYP3A4 activity is inhibited. Clarithromycin is an inhibitor of CYP3A4, whereas azithromycin is not.Objective: In older patients taking a CCB, we investigated whether coprescription of clarithromycin, compared with azithromycin, was associated with a higher risk of fracture.Methods: This was a population-level retrospective cohort study in Ontario, Canada, from 2003 to 2012 of older adults (mean age = 76 years) newly prescribed clarithromycin (n = 96 226) or azithromycin (n = 94 083) while taking a CCB (amlodipine, nifedipine, felodipine, verapamil, diltiazem). The outcome assessed within 30 days of a new coprescription was a nonvertebral fracture.Results: There were no differences in measured baseline characteristics between the clarithromycin and azithromycin groups. Amlodipine was the most commonly prescribed CCB (more than 50% of patients). Coprescribing clarithromycin, versus azithromycin, was not associated with a higher 30-day risk of nonvertebral fracture (124 patients of 96 226 taking clarithromycin [0.13%] vs 98 patients of 94 083 taking azithromycin [0.10%]; odds ratio = 1.23 [95% CI = 0.94-1.60]; P = 0.134).Conclusions: Among older adults taking a CCB, concurrent use of clarithromycin, compared with azithromycin, was not associated with a statistically significantly greater 30-day risk of nonvertebral fracture.